Electronic Health Records as Valuable Data Sources in the Health Care Quality Improvement Process. - Wikström, Katja; Toivakka, Maija; Rautiainen, Päivi; Tirkkonen, Hilkka; Repo, Teppo; Laatikainen, Tiina (Health Services Research and Managerial Epidemiology, 2019)
In North Karelia, Finland, the regional electronic health records (EHRs) enable flexible data retrieval and area-level analyses. The aim of this study was to assess the early detection of type 2 diabetes (T2D) in the region and to evaluate the performed activities in order to improve the processes between the years 2012 and 2017.